Polylactic acid composite fiber membrane as well as preparation method and application thereof
By constructing a non-good solvent-good solvent-polylactic acid system and using multi-needle electrospinning technology, a polylactic acid composite fiber membrane with high specific surface area and high surface potential was prepared, which solved the problem of poor filtration effect of existing fiber membranes and air pollution. The problem of high resistance significantly improves the air filtration effect.
Patent Information
- Application Number
- CN202411478891.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing polylactic fiber membranes have small specific surface area, low surface potential, poor filtration effect and high air resistance, making it difficult to effectively remove dust and fine particles in the air.
By constructing a system of non-good solvent-good solvent-polylacuric acid or polyclavic acid, two types of spinning fluid are prepared, and polymapiline composite fiber membrane is prepared with multi-needle static spinning technology. This method is separated by inducing phase to form a three -dimensional connecting pore structure, which improves the surface area and surface potential of the fiber membrane.
The prepared polylactic acid composite fiber membrane has high specific surface area, high surface potential, high filtration efficiency and low air resistance, which significantly improves the air filtration effect.
Smart Images

Figure CN119352234A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fully degradable fiber membrane materials for high-efficiency air filtration, and in particular to a polylactic acid composite fiber membrane, a preparation method and application thereof. Background Art
[0002] Dust and fine particles in the air pose a great threat to people's health. Metal dust exists in the atmosphere in the form of oxides, which helps to produce reactive oxygen, which damages cells and tissues and causes inflammation in the body. And these particles can cause genotoxic effects, cell membrane damage, lung and systemic cardiovascular diseases.
[0003] Fibrous air filtration membranes have been widely used to remove air pollutants. These devices perform well in particle collection, are cost-effective, and are easy to manufacture. Airborne particles pass through the filter media and are collected on the filter membrane through physical deposition mechanisms such as inertial impaction, interception, and Brownian diffusion.
[0004] Polylactic acid has good biodegradability. After use, it can be completely degraded by microorganisms in nature, and finally produces carbon dioxide and water without polluting the environment. This is very beneficial to environmental protection and is a recognized environmentally friendly material.
[0005] The prior art uses polylactic acid fiber membranes as air filtration membranes. However, the existing polylactic acid fiber membranes still have problems such as small specific surface area, poor filtration effect, and high air resistance.
[0006] Therefore, on this basis, it is necessary to research and develop a polylactic acid composite fiber membrane and its preparation method with high specific surface area and surface potential, good filtration effect and low air resistance, which is of great significance for reducing the harm of dust and fine particles to human health. Summary of the invention
[0007] The main purpose of the present invention is to provide a polylactic acid composite fiber membrane, a preparation method and application thereof, so as to solve the problems of small specific surface area, low surface potential, poor filtration effect and high air resistance of the polylactic acid composite fiber membrane in the prior art.
[0008] In order to achieve the above-mentioned purpose, the present invention provides a preparation method of a polylactic acid composite fiber membrane on the one hand, and the preparation method comprises: step S1, mixing poly-L-lactic acid with a first solvent to obtain a first spinning solution; step S2, mixing poly-D-lactic acid with a second solvent to obtain a second spinning solution; step S3, performing multi-needle electrospinning on the first spinning solution and the second spinning solution to obtain a polylactic acid composite fiber membrane; wherein the first solvent is a mixture of a good solvent and a non-good solvent of poly-L-lactic acid, the solubility of poly-L-lactic acid in its good solvent is ≥10g / mL, and the solubility in its non-good solvent is ≤50g / mL; the mass concentration of poly-L-lactic acid in the first spinning solution is 0.4-15wt%; the second solvent is a mixture of a good solvent and a non-good solvent of poly-D-lactic acid, the solubility of poly-D-lactic acid in its good solvent is ≥15g / mL, and the solubility in its non-good solvent is ≤55g / mL; the mass concentration of poly-D-lactic acid in the second spinning solution is 10-30wt%.
[0009] Furthermore, the first solvent is a mixture of a good solvent and a non-good solvent in a volume ratio of 1:(2-5); and the weight average molecular weight of the poly-L-lactic acid is 10-150 kDa.
[0010] Furthermore, the solubility of poly-L-lactic acid in its good solvent is 10-60 g / mL, and the solubility in its non-good solvent is 5-50 g / mL.
[0011] Further, the good solvent for poly-L-lactic acid is selected from one or more of the group consisting of dichloromethane, chloroform, dimethylformamide, N-methylpyrrolidone, hexafluoroisopropanol, ethyl acetate and tetrahydrofuran.
[0012] Furthermore, the non-good solvent for poly-L-lactic acid is selected from one or more of the group consisting of methanol, ethanol, isopropanol, glycerol, butanol, ethylene glycol and propylene glycol.
[0013] Furthermore, the second solvent is a mixture of a good solvent and a non-good solvent in a volume ratio of 1:(5-10); the weight average molecular weight of the poly (d-lactic acid) is 80-300 kDa.
[0014] Furthermore, the solubility of poly (D-lactic acid) in its good solvent is 15-65 g / mL, and the solubility in its non-good solvent is 10-55 g / mL.
[0015] Furthermore, the good solvent for poly (D-lactic acid) is selected from one or more of the group consisting of dichloromethane, chloroform, dimethylformamide, N-methylpyrrolidone, hexafluoroisopropanol, ethyl acetate and tetrahydrofuran.
[0016] Furthermore, the non-good solvent for poly (D-lactic acid) is selected from one or more of the group consisting of methanol, ethanol, isopropanol, glycerol, butanol, ethylene glycol and propylene glycol.
[0017] Furthermore, multi-needle electrospinning is carried out using an electrospinning device, in which at least two needles are provided. Preferably, the first spinning solution and the second spinning solution are electrospun simultaneously through the two needles respectively. Preferably, the diameter of each needle is 10 to 80 μm, and the moving speed of each needle is 5 to 50 mm / s.
[0018] Furthermore, during the multi-needle electrospinning process, the temperature is 20-40° C. and the ambient humidity is 25-45%.
[0019] Furthermore, during the multi-needle electrospinning process, the voltage is 10 to 30 kV and the receiving distance is 10 to 25 cm.
[0020] Furthermore, during the multi-needle electrospinning process, the volume of the first spinning solution is 2-10 mL, the consumption rate of the first spinning solution is 0.8-2 mL / h, the volume of the second spinning solution is 5-15 mL, and the consumption rate of the second spinning solution is 0.2-1.5 mL / h.
[0021] Furthermore, during the multi-needle electrospinning process, the voltage is 8 to 30 kV, the consumption rate of the first spinning solution is 0.8 to 2 mL / h, the consumption rate of the second spinning solution is 0.2 to 1.5 mL / h, and the receiving distance is 10 to 25 cm.
[0022] In order to achieve the above-mentioned purpose, another aspect of the present invention further provides a polylactic acid composite fiber membrane, which is prepared by the preparation method of the above-mentioned polylactic acid composite fiber membrane provided in the present application, and includes poly-L-lactic acid fiber and poly-D-lactic acid fiber.
[0023] Furthermore, the diameter of the poly L-lactic acid fiber is 30 to 900 nm, and the average pore size is 5 to 55 nm; preferably, the diameter of the poly D-lactic acid fiber is 50 to 950 nm, and the average pore size is 10 to 65 nm.
[0024] Furthermore, the thickness of the polylactic acid composite fiber membrane is 5 to 30 μm.
[0025] Furthermore, the specific surface area of the polylactic acid composite fiber membrane is 158.6 to 165.3 m 2 / g, surface potential is 11.3~14.5kV, breaking strength is 19.7~23.2MPa, PM 0.3 The filtration efficiency is 97.6-99.6%, PM 2.5 The filtration efficiency is 98.3-99.9%, and when the flow rate is 85L / min, the air resistance is ≤95Pa.
[0026] Another aspect of the present invention provides an air filter, which includes the polylactic acid composite fiber membrane produced by the above-mentioned preparation method provided in the present application, or the above-mentioned polylactic acid composite fiber membrane provided in the present application.
[0027] Applying the technical solution of the present invention, the present application constructs a "non-good solvent-good solvent-poly-L-lactic acid (PLLA)" or "non-good solvent-good solvent-poly-D-lactic acid (PDLA)" system, takes PLLA or PDLA as the matrix polymer, dissolves it in a mixed solvent of a good solvent and a non-good solvent, and obtains two spinning solutions (i.e., the first spinning solution and the second spinning solution), respectively, and performs multi-needle electrospinning on the two first spinning solutions and the second spinning solution to obtain a polylactic acid composite fiber membrane.
[0028] Compared with the preparation of spinning solution using only good solvent of PLLA or PDLA, the preparation of spinning solution using mixed solvent containing non-good solvent can induce phase separation so that the spun polylactic acid fibers can form a three-dimensional interconnected pore structure in situ, thereby making the prepared polylactic acid composite fiber membrane have high specific surface area, high surface potential, high filtration efficiency and low air resistance.
[0029] Multi-needle electrospinning generates a fluid jet by electrifying the spinning solution, and then stretches and solidifies to form ultrafine fibers with a diameter of tens of nanometers to several microns. By changing the spinning parameters and environmental conditions of the electrospinning process, customized pores including pores within the fiber, pores on the surface of the fiber, and pores between fibers can be accurately constructed and adjusted on a nanometer and micrometer scale. Moreover, electrospinning is cheap and has a wide variety of spinnable materials. Applying it in this application can reduce the preparation cost of polylactic acid composite fiber membranes. Compared with other mass concentrations, limiting the mass concentrations of the first spinning solution and the second spinning solution to the above range is beneficial to improving the efficiency of multi-needle electrospinning, and is also beneficial to improving the continuity of the fibers obtained by spinning, thereby helping to improve the specific surface area of the polylactic acid composite fiber membrane and the comprehensive performance of the air filtration effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0031] Figure 1 The SEM image of the polylactic acid fiber composite film prepared in Example 1 of the present invention is shown;
[0032] Figure 2 The SEM image of the polylactic acid fiber membrane prepared in Comparative Example 1 of the present invention is shown;
[0033] Figure 3The SEM image of the polylactic acid fiber membrane prepared in Comparative Example 2 of the present invention is shown. DETAILED DESCRIPTION
[0034] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0035] As described in the background art, the existing polylactic acid composite fiber membrane has the problems of small specific surface area, low surface potential, poor filtering effect and high air resistance, which makes it difficult to reduce the harm of dust and fine particles to human health. In order to solve the above-mentioned technical problems, the first aspect of the present application provides a method for preparing a polylactic acid composite fiber membrane, which comprises: step S1, mixing poly-L-lactic acid with a first solvent to obtain a first spinning solution; step S2, mixing poly-D-lactic acid with a second solvent to obtain a second spinning solution; step S3, performing multi-needle electrospinning on the first spinning solution and the second spinning solution to obtain a polylactic acid composite fiber membrane; wherein the first solvent is a mixture of a good solvent and a non-good solvent for poly-L-lactic acid, the solubility of poly-L-lactic acid in its good solvent is ≥10 g / mL, and the solubility in its non-good solvent is ≤50 g / mL; the mass concentration of poly-L-lactic acid in the first spinning solution is 0.4 to 15 wt%; the second solvent is a mixture of a good solvent and a non-good solvent for poly-D-lactic acid, the solubility of poly-D-lactic acid in its good solvent is ≥15 g / mL, and the solubility in its non-good solvent is ≤55 g / mL; the mass concentration of poly-D-lactic acid in the second spinning solution is 10 to 30 wt%.
[0036] The present application constructs a system of "non-good solvent-good solvent-poly-L-lactic acid (PLLA)" or "non-good solvent-good solvent-poly-D-lactic acid (PDLA)", takes PLLA or PDLA as a matrix polymer, dissolves it in a mixed solvent of a good solvent and a non-good solvent, and obtains two spinning solutions (i.e., a first spinning solution and a second spinning solution), respectively, and performs multi-needle electrospinning on the two first spinning solutions and the second spinning solution to obtain a polylactic acid composite fiber membrane.
[0037] Compared with the preparation of spinning solution using only good solvent of PLLA or PDLA, the preparation of spinning solution using mixed solvent containing non-good solvent can induce phase separation so that the spun polylactic acid fibers can form a three-dimensional interconnected pore structure in situ, thereby making the prepared polylactic acid composite fiber membrane have high specific surface area, high surface potential, high filtration efficiency and low air resistance.
[0038] Multi-needle electrospinning generates a fluid jet by electrifying the spinning solution, and then stretches and solidifies to form ultrafine fibers with a diameter of tens of nanometers to several microns. By changing the spinning parameters and environmental conditions of the electrospinning process, customized pores including pores within the fiber, pores on the surface of the fiber, and pores between fibers can be accurately constructed and adjusted on a nanometer and micrometer scale. Moreover, electrospinning is cheap and has a wide variety of spinnable materials. Applying it in this application can reduce the preparation cost of polylactic acid composite fiber membranes. Compared with other mass concentrations, limiting the mass concentrations of the first spinning solution and the second spinning solution to the above range is beneficial to improving the efficiency of multi-needle electrospinning, and is also beneficial to improving the continuity of the fibers obtained by spinning, thereby helping to improve the specific surface area of the polylactic acid composite fiber membrane and the comprehensive performance of the air filtration effect.
[0039] In a preferred embodiment, the first solvent is a mixture of a good solvent and a non-good solvent in a volume ratio of 1:(2-5); the weight average molecular weight of poly-L-lactic acid is 50-150 kDa. Compared with other ranges, limiting the components of the first solvent and the weight average molecular weight or degree of polymerization of PLLA within the above range is conducive to better exerting its inducing phase separation effect, thereby improving the pore structure of the polylactic acid composite fiber membrane, thereby increasing its specific surface area and surface potential, and thereby improving its air filtration effect.
[0040] In order to further exert its effect of inducing phase separation and further improve the dispersibility of PLLA in the first spinning solution, preferably, the solubility of poly-L-lactic acid in its good solvent is 10-60 g / mL, and the solubility in its non-good solvent is 5-50 g / mL.
[0041] In a preferred embodiment, the good solvent of poly-L-lactic acid includes, but is not limited to, one or more of the group consisting of dichloromethane, chloroform, dimethylformamide, N-methylpyrrolidone, hexafluoroisopropanol, ethyl acetate and tetrahydrofuran. Compared with other types, the use of the above-mentioned good solvents is conducive to improving the dispersibility of PLLA, thereby improving the uniformity of the first spinning solution.
[0042] In a preferred embodiment, the non-good solvent of poly-L-lactic acid includes, but is not limited to, one or more of the group consisting of methanol, ethanol, isopropanol, glycerol, butanol, ethylene glycol and propylene glycol. Compared with other types, the use of the above-mentioned non-good solvents is conducive to better exerting its inducing phase separation effect, thereby improving the pore structure of the polylactic acid composite fiber membrane, and further increasing its specific surface area and surface potential.
[0043] In a preferred embodiment, the second solvent is a mixture of a good solvent and a non-good solvent in a volume ratio of 1:(5-10); the weight average molecular weight of poly (d-lactic acid) is 80-300 kDa. Compared with other ranges, limiting the components of the second solvent and the weight average molecular weight or degree of polymerization of PDLA within the above range is conducive to better exerting its inducing phase separation effect, thereby improving the pore structure of the polylactic acid composite fiber membrane, and further increasing its specific surface area and surface potential.
[0044] In order to further exert its effect of inducing phase separation and further improve the dispersibility of PDLA in the second spinning solution, preferably, the solubility of poly (D-lactic acid) in its good solvent is 15-65 g / mL, and the solubility in its non-good solvent is 10-55 g / mL.
[0045] In a preferred embodiment, the good solvent of poly (d-lactic acid) includes, but is not limited to, one or more of the group consisting of dichloromethane, chloroform, dimethylformamide, N-methylpyrrolidone, hexafluoroisopropanol, ethyl acetate and tetrahydrofuran. Compared with other types, the use of the above-mentioned good solvents is conducive to improving the dispersibility of PDLA, thereby improving the uniformity of the first spinning solution.
[0046] In a preferred embodiment, the non-good solvent of poly (d-lactic acid) includes, but is not limited to, one or more of the group consisting of methanol, ethanol, isopropanol, glycerol, butanol, ethylene glycol and propylene glycol. Compared with other types, the use of the above-mentioned non-good solvents is conducive to better exerting its inducing phase separation effect, thereby improving the pore structure of the poly (lactic acid) composite fiber membrane, and further increasing its specific surface area and surface potential.
[0047] In a preferred embodiment, the multi-needle electrospinning is performed using an electrospinning device, in which at least two needles are provided, and preferably, the first spinning solution and the second spinning solution are electrospun simultaneously through the two needles. With respect to the preparation method provided in the present application, using two needles to electrospin the first spinning solution and the second spinning solution simultaneously is conducive to compounding the PLLA fiber with the PDLA fiber, thereby facilitating the acquisition of a polylactic acid composite fiber membrane.
[0048] In order to further improve the pore structure in the polylactic acid composite fiber membrane, thereby further improving the specific surface area and surface potential of the polylactic acid composite fiber membrane, and further improving its air filtration effect, preferably, the diameter of each needle is 10 to 80 μm, and the moving speed of each needle is 5 to 50 mm / s.
[0049] In a preferred embodiment, during the multi-needle electrospinning process, the temperature is 20-40°C and the ambient humidity is 25-45%. The ambient humidity includes but is not limited to the above range, and limiting it within the above range is beneficial to improving the specific surface area of the polylactic acid composite fiber membrane.
[0050] In a preferred embodiment, during the multi-needle electrospinning process, the voltage is 10 to 30 kV and the receiving distance is 10 to 25 cm. During the multi-needle electrospinning process, the voltage and the receiving distance include but are not limited to the above ranges. Limiting them within the above ranges is conducive to making the spun PLLA fibers and PDLA fibers more continuous, and is conducive to inhibiting fiber breakage, thereby increasing the specific surface area and surface potential of the polylactic acid composite fiber membrane, and further improving its air filtration effect.
[0051] It should be noted that the receiving distance in the present application refers to the distance between the needle tip and the receiving substrate, and the polylactic acid composite fiber membrane obtained by multi-needle electrospinning is formed on the surface of the receiving substrate on one side close to the needle tip.
[0052] During the electrospinning process, the spinning solution will be gradually consumed as the electrospinning proceeds. In a preferred embodiment, during multi-needle electrospinning, the volume of the first spinning solution is 2 to 10 mL, the consumption rate of the first spinning solution is 0.8 to 2 mL / h, the volume of the second spinning solution is 5 to 15 mL, and the consumption rate of the second spinning solution is 0.2 to 1.5 mL / h. The volume of the first spinning solution and the second spinning solution and their respective consumption rates include but are not limited to the above ranges, respectively. Limiting them within the above ranges is beneficial to improving the continuity of the prepared PLLA fiber and PDLA fiber, and is beneficial to inhibiting fiber breakage, thereby increasing the specific surface area and surface potential of the polylactic acid composite fiber membrane, and further improving its air filtration effect.
[0053] In order to further increase the specific surface area and surface potential of the polylactic acid composite fiber membrane, thereby further improving its air filtration effect, preferably, during the multi-needle electrospinning process, the voltage is 8 to 30 kV, the consumption rate of the first spinning solution is 0.8 to 2 mL / h, the consumption rate of the second spinning solution is 0.2 to 1.5 mL / h, and the receiving distance is 10 to 25 cm.
[0054] The second aspect of the present application also provides a polylactic acid composite fiber membrane, which is prepared by the preparation method of the polylactic acid composite fiber membrane provided by the present application, and includes poly-L-lactic acid fiber and poly-D-lactic acid fiber. The polylactic acid composite fiber membrane provided by the present application has a high specific surface area and surface potential, and has excellent air filtration effect.
[0055] In order to further improve the mechanical properties and air filtration performance of the polylactic acid composite fiber membrane, preferably, the diameter of the poly-L-lactic acid fiber is 30-900nm, and the average pore size is 5-55nm; the diameter of the poly-D-lactic acid fiber is 50-950nm, and the average pore size is 10-65nm.
[0056] In order to further improve the air filtration effect of the polylactic acid composite fiber membrane, preferably, the thickness of the polylactic acid composite fiber membrane is 5 to 30 μm.
[0057] In a preferred embodiment, the specific surface area of the polylactic acid composite fiber membrane is 158.6 to 165.3 m 2 / g, surface potential is 11.3~14.5kV, breaking strength is 19.7~23.2MPa, PM 0.3 The filtration efficiency is 97.6-99.6%, PM 2.5 The filtration efficiency is 98.3-99.9%, and when the flow rate is 85L / min, the air resistance is ≤95Pa.
[0058] The third aspect of the present application also provides an air filter, which includes the polylactic acid composite fiber membrane prepared by the above preparation method provided in the present application, or the above polylactic acid composite fiber membrane. The polylactic acid composite fiber membrane provided in the present application has a high specific surface area and surface potential, and its application in the air filter can significantly improve the air filtration effect.
[0059] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0060] Example 1
[0061] A method for preparing a polylactic acid composite fiber membrane:
[0062] (1) mixing 180 mg of PLLA having a weight average molecular weight of 80 kDa with 4 mL of a first solvent to obtain 4 mL of a first spinning solution, wherein the first solvent is a good solvent of dichloromethane and a non-good solvent of methanol in a volume ratio of 1:4, and the mass concentration of PLLA in the first spinning solution is 5 wt%;
[0063] (2) mixing 1053 mg of PDLA having a weight average molecular weight of 150 kDa with 8 mL of a second solvent to obtain 8 mL of a second spinning solution, wherein the second solvent is a good solvent chloroform and a non-good solvent ethanol in a volume ratio of 1:8, and the mass concentration of PDLA in the second spinning solution is 15 wt %;
[0064] (3) Multi-needle electrospinning was carried out using a multi-needle electrospinning device (China Tongli, model TL-Pro-BM). The device was provided with two needles. The diameter of the needle used for spinning the first spinning solution (counted as needle A) was 15 μm, and the diameter of the needle used for spinning the second spinning solution (counted as needle B) was 45 μm. The voltage was set to 15 kV, and the receiving substrate was set at a receiving distance of 20 cm. The temperature was 20°C, and the ambient humidity was 30%. During the multi-needle electrospinning process, the movement rate of needle A was 10 mm / s, and the movement rate of needle B was 30 mm / s. The consumption rate of the first spinning solution was 1 mL / h, and the consumption rate of the second spinning solution was 0.5 mL / h, to obtain a polylactic acid composite fiber membrane with a thickness of 10 μm.
[0065] like Figure 1 As shown, the polylactic acid composite fiber membrane has composite fibers arranged in a staggered manner, and the fibers have a porous structure.
[0066] Example 2
[0067] The difference from Example 1 is that the mass concentration of PLLA in the first spinning solution is 0.4 wt %.
[0068] Example 3
[0069] The difference from Example 1 is that the mass concentration of PLLA in the first spinning solution is 15 wt %.
[0070] Example 4
[0071] The difference from Example 1 is that in step (1), the first solvent is a mixed solvent of dichloromethane and methanol in a volume ratio of 1:2.
[0072] Example 5
[0073] The difference from Example 1 is that in step (1), the first solvent is a mixed solvent of dichloromethane and methanol in a volume ratio of 1:5.
[0074] Example 6
[0075] The difference from Example 1 is that in step (1), the first solvent is a mixed solvent of dichloromethane and methanol in a volume ratio of 1:8.
[0076] Comparative Example 1
[0077] The difference from Example 1 is that step (2) is omitted, and single-needle electrospinning is used instead of multi-needle electrospinning in step (3), specifically:
[0078] PLLA with a weight average molecular weight of 80 kDa was dissolved in a mixed solvent of dichloromethane and glycerol (the volume ratio of dichloromethane and glycerol was 1:3) to obtain a spinning solution with a mass concentration of 0.5 wt%, followed by single-needle electrospinning. In the single-needle electrospinning process, the diameter of the needle was 10 μm, 2 mL of spinning solution was taken, the electrospinning voltage was set to 8 kV, the spinning temperature was 20 ° C, the relative humidity of the environment was 25%, the spinning solution consumption rate was 0.8 mL / h, the receiving distance was 10 cm, and the average diameter of the PLLA fiber obtained by electrospinning was 30 nm, the average pore size of the PLLA fiber membrane was 5 nm, and the thickness was 5 μm.
[0079] like Figure 2 As shown, the PLLA fiber membrane has fibers arranged in a staggered manner, and the fibers have a porous structure and uneven fiber diameters.
[0080] Comparative Example 2
[0081] The difference from Example 1 is that step (1) is omitted, and single-needle electrospinning is used instead of multi-needle electrospinning in step (3), specifically:
[0082] PDLA with a weight average molecular weight of 80 kDa was dissolved in a mixed solvent of dichloromethane and glycerol (the volume ratio of dichloromethane and glycerol was 1:6) to obtain a spinning solution with a mass concentration of 10 wt%, followed by single-needle electrospinning. In the single-needle electrospinning process, the diameter of the needle was 55 μm, 6 mL of spinning solution was taken, the electrospinning voltage was set to 12 kV, the spinning temperature was 25 ° C, the relative humidity of the environment was 30%, the spinning solution consumption rate was 1.2 mL / h, the receiving distance was 15 cm, and the average diameter of the PDLA fiber obtained by electrospinning was 80 nm, the average pore size of the PDLA fiber membrane was 10 nm, and the thickness was 15 μm.
[0083] like Figure 3 As shown, the PDLA fiber membrane has fibers arranged in a staggered manner, and the fibers have a porous structure and uneven fiber diameters.
[0084] Comparative Example 3
[0085] The difference from Example 1 is that the mass concentration of PLLA in the first spinning solution is 16 wt %.
[0086] Comparative Example 4
[0087] The difference from Example 1 is that the mass concentration of PDLA in the second spinning solution is 8 wt %.
[0088] Structural characterization and performance testing
[0089] Tensile performance test: The polylactic acid composite fiber membrane prepared in the embodiment of the present application and the PLLA fiber membrane or PDLA fiber membrane prepared in the comparative example were cut to obtain tensile specimens, and the tensile performance test was performed using a universal tensile machine (model 4403, sensor 100N) of Instron Company of the United States according to the plastic tensile performance test standard ASTM D638-2003 of the American Society for Testing and Materials. At least 3 parallel test samples were guaranteed for each group, and the results were averaged.
[0090] Specific surface area test: The nitrogen adsorption isotherm was measured at 77 K using a gas adsorption instrument (ASAP 2060, Micromeritics, USA).
[0091] Surface potential test: A non-contact electrostatic meter (VM54XQS, Quatek, USA) was used to test the surface potential of the polylactic acid composite fiber membrane prepared in the example of the present application and the PLLA fiber membrane or PDLA fiber membrane prepared in the comparative example. The test height was 2 cm, the temperature and humidity were constant at 25°C and 45%, and 20 data points were randomly collected for each sample and the average value was taken.
[0092] Filtration performance test: The fiber membrane (area 113.04cm 2 ) air filtration performance, the gas flow rate was set to 85L / min, and the particle size range of NaCl atomized particles produced by the aerosol generator was 0.1-10μm. At least 3 different positions of each group of fiber membranes were tested, and the results were averaged.
[0093] The test results of the above performances are shown in Table 1.
[0094] Table 1
[0095]
[0096] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0097] The present application constructs a system of "non-good solvent-good solvent-poly-L-lactic acid (PLLA)" or "non-good solvent-good solvent-poly-D-lactic acid (PDLA)", takes PLLA or PDLA as a matrix polymer, dissolves it in a mixed solvent of a good solvent and a non-good solvent, and obtains two spinning solutions (i.e., a first spinning solution and a second spinning solution), respectively, and performs multi-needle electrospinning on the two first spinning solutions and the second spinning solution to obtain a polylactic acid composite fiber membrane.
[0098] Compared with the preparation of spinning solution using only good solvent of PLLA or PDLA, the preparation of spinning solution using mixed solvent containing non-good solvent can induce phase separation so that the spun polylactic acid fibers can form a three-dimensional interconnected pore structure in situ, thereby making the prepared polylactic acid composite fiber membrane have high specific surface area, high surface potential, high filtration efficiency and low air resistance.
[0099] Compared with other mass concentrations, limiting the mass concentrations of the first spinning solution and the second spinning solution within the above-mentioned ranges is beneficial to improving the efficiency of multi-needle electrospinning, and at the same time is beneficial to improving the continuity of the fibers obtained by spinning, thereby helping to improve the comprehensive performance of the polylactic acid composite fiber membrane, such as the specific surface area and air filtration effect.
[0100] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.
[0101] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a polylactic acid composite fiber membrane, characterized in that: The preparation method comprises: Step S1, mixing poly-L-lactic acid with a first solvent to obtain a first spinning solution; Step S2, mixing poly (d-lactic acid) with a second solvent to obtain a second spinning solution; Step S3, performing multi-needle electrospinning on the first spinning solution and the second spinning solution to obtain the polylactic acid composite fiber membrane; The first solvent is a mixture of a good solvent and a non-good solvent for the poly-L-lactic acid, the solubility of the poly-L-lactic acid in the good solvent is ≥10 g / mL, and the solubility in the non-good solvent is ≤50 g / mL; the mass concentration of the poly-L-lactic acid in the first spinning solution is 0.4-15 wt%; The second solvent is a mixture of a good solvent and a non-good solvent for the poly (D-lactic acid), the solubility of the poly (D-lactic acid) in its good solvent is ≥15 g / mL, and the solubility in its non-good solvent is ≤55 g / mL; the mass concentration of the poly (D-lactic acid) in the second spinning solution is 10-30 wt%.
2. The method for preparing the polylactic acid composite fiber membrane according to claim 1, characterized in that: The first solvent is a mixture of a good solvent and a non-good solvent in a volume ratio of 1:(2-5); the weight average molecular weight of the poly-L-lactic acid is 10-150 kDa; Preferably, the solubility of the poly-L-lactic acid in its good solvent is 10 to 60 g / mL, and the solubility in its non-good solvent is 5 to 50 g / mL; Preferably, the good solvent for poly-L-lactic acid is selected from one or more of the group consisting of dichloromethane, chloroform, dimethylformamide, N-methylpyrrolidone, hexafluoroisopropanol, ethyl acetate and tetrahydrofuran; Preferably, the non-good solvent for poly-L-lactic acid is selected from one or more of the group consisting of methanol, ethanol, isopropanol, glycerol, butanol, ethylene glycol and propylene glycol.
3. The method for preparing a polylactic acid composite fiber membrane according to claim 1 or 2, characterized in that: The second solvent is a mixture of a good solvent and a non-good solvent in a volume ratio of 1:(5-10); the weight average molecular weight of the poly (d-lactic acid) is 80-300 kDa; Preferably, the solubility of the poly(D-lactic acid) in its good solvent is 15 to 65 g / mL, and the solubility in its non-good solvent is 10 to 55 g / mL; Preferably, the good solvent for poly (d-lactic acid) is selected from one or more of the group consisting of dichloromethane, chloroform, dimethylformamide, N-methylpyrrolidone, hexafluoroisopropanol, ethyl acetate and tetrahydrofuran; Preferably, the non-good solvent for poly (D-lactic acid) is selected from one or more of the group consisting of methanol, ethanol, isopropanol, glycerol, butanol, ethylene glycol and propylene glycol.
4. The method for preparing the polylactic acid composite fiber membrane according to claim 1, characterized in that: The multi-needle electrospinning is performed by an electrospinning device, wherein at least two needles are provided in the electrospinning device, and preferably, the first spinning solution and the second spinning solution are electrospun simultaneously by two needles, preferably, the diameter of each needle is 10 to 80 μm, and the moving speed of each needle is 5 to 50 mm / s; Preferably, during the multi-needle electrospinning process, the temperature is 20-40° C. and the ambient humidity is 25-45%.
5. The method for preparing a polylactic acid composite fiber membrane according to any one of claims 1 to 4, characterized in that: During the multi-needle electrospinning process, the voltage is 10 to 30 kV and the receiving distance is 10 to 25 cm.
6. The method for preparing the polylactic acid composite fiber membrane according to claim 5, characterized in that: During the multi-needle electrospinning process, the volume of the first spinning solution is 2-10 mL, the consumption rate of the first spinning solution is 0.8-2 mL / h, the volume of the second spinning solution is 5-15 mL, and the consumption rate of the second spinning solution is 0.2-1.5 mL / h.
7. The method for preparing the polylactic acid composite fiber membrane according to claim 6, characterized in that: During the multi-needle electrospinning process, the voltage is 8 to 30 kV, the consumption rate of the first spinning solution is 0.8 to 2 mL / h, the consumption rate of the second spinning solution is 0.2 to 1.5 mL / h, and the receiving distance is 10 to 25 cm.
8. A polylactic acid composite fiber membrane, characterized in that: The polylactic acid composite fiber membrane is prepared by the preparation method of the polylactic acid composite fiber membrane according to any one of claims 1 to 7, and comprises poly-L-lactic acid fiber and poly-D-lactic acid fiber.
9. The polylactic acid composite fiber membrane according to claim 8, characterized in that: The diameter of the poly L-lactic acid fiber is 30 to 900 nm, and the average pore size is 5 to 55 nm; preferably, the diameter of the poly D-lactic acid fiber is 50 to 950 nm, and the average pore size is 10 to 65 nm; Preferably, the thickness of the polylactic acid composite fiber membrane is 5 to 30 μm; Preferably, the specific surface area of the polylactic acid composite fiber membrane is 158.6 to 165.3 m 2 / g, surface potential is 11.3~14.5kV, breaking strength is 19.7~23.2MPa, PM 0.3 The filtration efficiency is 97.6-99.6%, PM 2.5 The filtration efficiency is 98.3-99.9%, and when the flow rate is 85L / min, the air resistance is ≤95Pa.
10. An air filter, characterized in that: The air filter comprises the polylactic acid composite fiber membrane obtained by the preparation method according to any one of claims 1 to 7, or the polylactic acid composite fiber membrane according to claim 8 or 9.
Citation Information
Patent Citations
Preparation method of porous polylactic acid fiber
CN106637523A
Electrostatic spinning preparation method of porous polylactic acid fiber oil absorption material
CN112725906A
Composite nano fiber endless tow preparing apparatus and its preparing method
CN1776033A
Nonwoven fabric and process for producing the same
CN1833063A
Biodegradable nonwoven fabric and its production
JP1996325912A